Polyphenols as fungal phytotoxins, seed germination stimulants and phytoalexins - Cimmino, Alessio; Andolfi, Anna; Abouzeid, Mohamed; Evidente, Antonio (PHYTOCHEMISTRY REVIEWS, 2013)
This review deals with the sources and chemical and biological characterization of phytotoxic polyphenols produced essentially by pathogenic fungi of forest and crop plants and of weeds. Their potential use as natural herbicides and fungicides is discussed. The use of some polyphenols which could be applied as an alternative method to control parasitic weeds, the so called ``suicidal germination{''}, will be covered. The sources and the isolation and identification of polyphenols produced by some crop plants in consequence of the attack of pathogenic fungi as plant defence compounds (phytoalexins), are also described.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Phytoalexins; Phytotoxins; polyphenols; Seed germination stimulants

Afritoxinones A and B, dihydrofuropyran-2-ones produced by Diplodia africana the causal agent of branch dieback on Juniperus phoenicea - Evidente, Antonio; Masi, Marco; Linaldeddu, Benedetto T.; Franceschini, Antonio; Scanu, Bruno; Cimmino, Alessio; Andolfi, Anna; Motta, Andrea; Maddau, Lucia (PHYTOCHEMISTRY, 2012)
Two phytotoxic dihydrofuropyran-2-ones, named afritoxinones A and B. were isolated from liquid culture of Diplodia africana. a fungal pathogen responsible for branch dieback of Phoenicean juniper in Italy. Additionally, six others known metabolites were isolated and characterized: oxysporone, sphaeropsidin A, epi-sphaeropsidone, R-(-)-mellein, (3R,4R)-4-hydroxymellein and (3R,4S)-4-hydroxymellein. The structures of afritoxinones A and B were established by spectroscopic and optical methods and determined to be as (3aS{*},6R{*}-,7aS)-6-methoxy-3a,7a-dihydro-3H,6H-furo\{[\}2,3-b]pyran-2-o ne and (3aR{*},6R{*},7aS)-6-methoxy-3a,7a-dihydro-3H,6H-furo\{[\}2,3-b]pyran-2-on e, respectively. The phytotoxic activity of afritoxinones A and B and oxysporone was evaluated on host (Phoenicean juniper) and non-host plant (holm oak, cork oak and tomato) by cutting and leaf puncture assay. Oxysporone proved to be the most phytotoxic compound. This study represents the first report of secondary metabolites produced by D. africana. In addition, the taxonomic implications of secondary metabolites in Botryosphaeriaceae family studies are discussed. (C) 2012 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: Afritoxinones A and B; Botryosphaeriaceae; Diplodia africana; Juniperus phoenicea; Phytotoxins

Relationships between the stereochemistry and biological activity of fungal phytotoxins - Evidente, Antonio; Andolfi, Anna; Cimmino, Alessio (Chirality, 2011)
Toxins produced by phytopathogenic fungi assume great importance because of their involvement in several plant diseases. Although such pathogens are known to have seriously damaged crops, forest, and environmental resources, they represent a very important tool to develop new environmentally friendly herbicides and fungicides. This review deals with the relationships between the biological activity of some phytotoxins produced by pathogenic fungi for major forest plants and for damaging weeds and their stereochemistry. In particular, the methods used to determine their relative and/or absolute configuration will be illustrated. These include the application of Mosher's and Murata's methods, X-ray diffractometric analysis, circular dichroism, and the use of computational methods to determine the theoretical optical rotatory power as well as the CD spectrum. The importance of determining the absolute configuration to achieve the total synthesis of some phytotoxins, interesting for their potential practical application, is also discussed. Chirality, 2011. © 2011 Wiley-Liss, Inc.
The following values have no corresponding Zotero field: publisher: Wiley Subscription Services, Inc., A Wiley Company
Keywords: Phytopathogenic fungi; Phytotoxins; relative and/or absolute configuration; structure–activity relationships

Diplopyrone, a New Phytotoxic Tetrahydropyranpyran-2-one Produced by Diplodia mutila, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Maddau, Lucia; Spanu, Emanuela; Franceschini, Antonio; Lazzaroni, Silvia; Motta, Andrea (Journal of Natural Products, 2003)
A new phytotoxic monosubstituted tetrahydropyranpyran-2-one, named diplopyrone (1), was isolated from the liquid culture filtrates of Diplodia mutila, a plant pathogenic fungus causing a form of canker disease of cork oak (Quercus suber). Diplopyrone was characterized, using spectroscopic and chemical methods, as 6-[(1S)-1-hydroxyethyl]-2,4a,6,8a-tetrahydropyran[3,2-b]pyran-2-one. The absolute stereochemistry of the chiral secondary hydroxylated carbon (C-9), determined by application of Mosher's method, proved to be S. Diplopyrone assayed at a 0.01?0.1 mg/mL concentration range caused necrosis and wilting on cork oak cuttings. On a nonhost plant, tomato, diplopyrone caused brown discoloration or stewing on the stem.
Keywords: Phytopathogenic fungi; Phytotoxins; relative and/or absolute configuration; structure–activity relationships

Diplopyrone, a New Phytotoxic Tetrahydropyranpyran-2-one Produced by Diplodia mutila, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Maddau, Lucia; Spanu, Emanuela; Franceschini, Antonio; Lazzaroni, Silvia; Motta, Andrea (Journal of Natural Products, 2003)
A new phytotoxic monosubstituted tetrahydropyranpyran-2-one, named diplopyrone (1), was isolated from the liquid culture filtrates of Diplodia mutila, a plant pathogenic fungus causing a form of canker disease of cork oak (Quercus suber). Diplopyrone was characterized, using spectroscopic and chemical methods, as 6-[(1S)-1-hydroxyethyl]-2,4a,6,8a-tetrahydropyran[3,2-b]pyran-2-one. The absolute stereochemistry of the chiral secondary hydroxylated carbon (C-9), determined by application of Mosher's method, proved to be S. Diplopyrone assayed at a 0.01?0.1 mg/mL concentration range caused necrosis and wilting on cork oak cuttings. On a nonhost plant, tomato, diplopyrone caused brown discoloration or stewing on the stem.
The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 12608876
Keywords: Phytopathogenic fungi; Phytotoxins; relative and/or absolute configuration; structure–activity relationships